2016
DOI: 10.1016/j.jhep.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after successful direct-acting antiviral therapy for patients with chronic hepatitis C and decompensated cirrhosis

Abstract: Cheung, M. C. M. et al. (2016) Outcomes after successful direct-acting antiviral therapy for patients with chronic hepatitis C and decompensated cirrhosis. Journal of Hepatology, 65(4), pp. 741-747. (doi:10.1016Hepatology, 65(4), pp. 741-747. (doi:10. /j.jhep.2016 This is the author's final accepted version.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/123893/ There was no signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
353
5
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(385 citation statements)
references
References 15 publications
21
353
5
6
Order By: Relevance
“…Treatment should be initiated as soon as possible in order to complete a full treatment course and achieve SVR before LT [3,4]. A benefit of SVR may be a significant improvement of liver function, leading to temporary inactivation or even delisting of selected cases [5,6] [B1]; -Treatment regimens including an NS3/4A protease inhibitor, such as Simeprevir, ritonavir-boosted Paritaprevir or Grazoprevir, are contraindicated in patients with ChildPugh B and C decompensated cirrhosis and in compensated cirrhosis with previous episodes of decompensation, because of the substantially higher protease inhibitor exposure in these patients [A1]; -Only Sofosbuvir-based regimens are recommended: 1) Sofosbuvir plus Ledipasvir, 2) Sofosbuvir plus Daclatasvir, or 3) Sofosbuvir plus Velpatasvir with daily weight-based ribavirin (RBV) (1000 or 1200 mg if body weight is <75 kg or >75 kg, respectively). RBV should be initiated at a low dose of 600 mg per day, increased subsequently depending on patient's tolerability Patients with a MELD score >18-20 in LT programs where the waiting time to transplant exceeds 6 months can be treated cautiously before LT [B1] [2,3].…”
Section: Patients With Decompensated Cirrhosis Without Hcc Awaiting Ltmentioning
confidence: 99%
“…Treatment should be initiated as soon as possible in order to complete a full treatment course and achieve SVR before LT [3,4]. A benefit of SVR may be a significant improvement of liver function, leading to temporary inactivation or even delisting of selected cases [5,6] [B1]; -Treatment regimens including an NS3/4A protease inhibitor, such as Simeprevir, ritonavir-boosted Paritaprevir or Grazoprevir, are contraindicated in patients with ChildPugh B and C decompensated cirrhosis and in compensated cirrhosis with previous episodes of decompensation, because of the substantially higher protease inhibitor exposure in these patients [A1]; -Only Sofosbuvir-based regimens are recommended: 1) Sofosbuvir plus Ledipasvir, 2) Sofosbuvir plus Daclatasvir, or 3) Sofosbuvir plus Velpatasvir with daily weight-based ribavirin (RBV) (1000 or 1200 mg if body weight is <75 kg or >75 kg, respectively). RBV should be initiated at a low dose of 600 mg per day, increased subsequently depending on patient's tolerability Patients with a MELD score >18-20 in LT programs where the waiting time to transplant exceeds 6 months can be treated cautiously before LT [B1] [2,3].…”
Section: Patients With Decompensated Cirrhosis Without Hcc Awaiting Ltmentioning
confidence: 99%
“…However, individuals who are chronically infected but remain untreated have the highest risk of developing liver cirrhosis and HCC. Recent clinical studies show that an HCV cure using DAA‐based antiviral therapy among patients with advanced liver cirrhosis does not eliminate HCC risk 1, 2, 3. The incidence of HCC after a viral cure with a DAA‐based therapy was found to be much higher than that of the earlier findings with an interferon (IFN)‐based antiviral therapy 4.…”
Section: Introductionmentioning
confidence: 98%
“…Further studies showed comparable SVR rates among patients with advanced liver disease, as well as improvement in disease severity (namely improvement in MELD and CHILD scores). Such results were found early after the end of the treatment (5,6).…”
mentioning
confidence: 56%